Sharia Students’ Perspectives on Qur’an Recitation and Its English Translation as A Disciplinary Measure for Tardiness - Pratiwi, Dian; Fransiska, Fini Widya; Haryono, Haryono; Maghfuri, Syukron (English Education and Literature Journal (E-Jou), 2026)
This study aims to explore the perspectives of Sharia Economic Law students on the practice of Qur’an recitation and its English translation as a disciplinary measure for classroom tardiness. The policy, implemented by an Islamic higher education institution, adopts an educational approach grounded in religious values to instill discipline while enhancing Qur’anic literacy and students’ English proficiency. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews and observations involving students who had undergone the disciplinary action. The findings reveal that most students view the policy as a constructive form of guidance aligned with Sharia principles. They believe the practice contributes positively to improving discipline, strengthening spiritual awareness, and enhancing foreign language comprehension. However, some students expressed concerns regarding its psychological impact and questioned its effectiveness as a sanction. The study recommends periodic evaluations of the policy to ensure its implementation remains consistent with the principles of justice, Islamic values, and a humanistic educational approach.